2010
DOI: 10.1128/aem.00027-10
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of OmcZ, an Outer-Surface, Octaheme c -Type Cytochrome Essential for Optimal Current Production by Geobacter sulfurreducens

Abstract: Previous studies have demonstrated that Geobacter sulfurreducens requires the c-type cytochrome OmcZ, which is present in large (OmcZ L ; 50-kDa) and small (OmcZ S ; 30-kDa) forms, for optimal current production in microbial fuel cells. This protein was further characterized to aid in understanding its role in current production. Subcellular-localization studies suggested that OmcZ S was the predominant extracellular form of OmcZ. N-and C-terminal amino acid sequence analysis of purified OmcZ S and molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
185
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(218 citation statements)
references
References 64 publications
24
185
2
1
Order By: Relevance
“…Such biofilms are electrically conductive, inferred by the ability of cells not in direct contact with the anode surface to contribute to current generation (22), and confirmed by two-electrode conductivity measurements (20,23). Geobacter cells possess an abundance of multiheme c-type cytochromes on their outer membrane, in the ECM, and along PilApili (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Cyclic voltammetry (19,(34)(35)(36)(37) and spectroelectrochemical measurements (38)(39)(40)(41)(42)(43) of actively respiring Geobacter biofilms are consistent with long-range electron transport mediated by sequential electron transfer reactions through a network of bound redox cofactors comprised of ECM c-type cytochromes terminating with electron transfer to the anode surface.…”
mentioning
confidence: 83%
“…Such biofilms are electrically conductive, inferred by the ability of cells not in direct contact with the anode surface to contribute to current generation (22), and confirmed by two-electrode conductivity measurements (20,23). Geobacter cells possess an abundance of multiheme c-type cytochromes on their outer membrane, in the ECM, and along PilApili (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Cyclic voltammetry (19,(34)(35)(36)(37) and spectroelectrochemical measurements (38)(39)(40)(41)(42)(43) of actively respiring Geobacter biofilms are consistent with long-range electron transport mediated by sequential electron transfer reactions through a network of bound redox cofactors comprised of ECM c-type cytochromes terminating with electron transfer to the anode surface.…”
mentioning
confidence: 83%
“…Gene deletion studies have suggested that the outer membrane surface c-type cytochrome OmcZ (GSU2076) is important for growth on current-harvesting anodes (Inoue et al, 2010Nevin et al, 2009;Richter et al, 2009). omcZ was upregulated during growth on Mn(IV) oxide but not Fe(III) oxide (Table 4).…”
Section: Anaerobic Respiration Of Insoluble Metal Oxidesmentioning
confidence: 99%
“…For example, whole-genome microarray comparisons of gene transcript abundance in current-producing biofilms versus biofilms reducing fumarate revealed that the octahaem c-type cytochrome OmcZ was one of the most highly expressed genes in current-producing biofilms . Subsequent gene deletion studies demonstrated that OmcZ was required for effective current production Richter et al, 2009) and further characterization demonstrated that OmcZ is an outer surface protein that is specifically localized at the biofilm-anode interface in current-producing biofilms (Inoue et al, 2010. In a previous study, Fe(III) reduction pathways were investigated by comparing gene expression in G. sulfurreducens growing with Fe(III) chelated with citrate as the electron acceptor and cells growing by fumarate reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, direct electron transfer differs when the extracellular electron acceptor is soluble. For instance, OmcS and pili are not required for reduction of Fe(III) citrate by Geobacter whereas OmcZ is 11,28 .…”
Section: (2) Direct Eetmentioning
confidence: 99%